PLACE OF INTENSIVE METHODS IN THE SYSTEM OF TEACHING FOREIGN LANGUAGE IN THE ACADEMIC LYCEUMS (Archive of Conferences, 2022)
One of the leading tendencies of modern teaching methods of foreign languages is the search for such teaching methods that would most fully correspond to the set goals. The problem of choosing the right method and method of teaching is quite complicated. It has always caused certain difficulties when working, especially for young and novice teachers. The goal of this article is to study the development of various methods and techniques in foreign and domestic methods, to identify modern methods